Representations of the symmetric groups and the Clebsch—Gordan coefficients of the unitary groups - Jucys, A. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. А. Юцис. Представления симметрических групп и коэффициенты Клебша—Гордана унитарных групп A. Jucys. Simetrinių grupių atvaizdavimai ir unitarinių grupių Klebšo—Gordano koeficientai